Gunshot wound causing thoracic aortic injury with bullet embolization to the common femoral artery - Mira T. Tanenbaum, MD; Mary Matecki, MD; Shawn Sarin, MD; Susan Kartiko, MD, PhD; Farhan Ayubi, MD; Salim Lala, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Penetrating traumatic aortic injury (PTAI) is increasing in prevalence given the rise in firearm violence in the United States and is associated with significant morbidity and mortality. These injuries often result in hemorrhagic shock, with patients presenting in extremis or pulseless, traditionally requiring open approaches for repair. A rare but potentially devastating complication of firearm-related PTAI is bullet embolization. This case report describes the successful resuscitation and endovascular treatment of a patient with a firearm-induced PTAI complicated by acute limb ischemia secondary to bullet arterial embolization to the common femoral artery requiring arteriotomy for bullet removal.